High-Speed Swimsuits and Their Historical Development in Competitive Swimming - Trinidad Morales, Alfonso; Tamayo Fajardo, Javier Antonio; González-García, Higinio (Frontiers in Psychology, 2020)
The goal of this research was to review the experimental studies that have analyzed the influence of “high-speed swimsuits” on sports performance up to the appearance of the model “Jammer” in competitive swimmers. The design was a review following PRISMA Methodology, in which 43 studies were reviewed of a total of 512. Several searches were conducted in electronic databases of the existing research in this field (Google Scholar, Dialnet, Web of Sciences, and Scopus). The only studies excluded were those that reviewed the effects with neoprene and tests with triathletes. The studies that were included were published and peer-reviewed from 1999 to 2018 in which the effect of high-speed swimsuits was analyzed. The results showed the possible effects that high-speed swimwear can have in relation or not to competitive performance, biomechanical, physiological and psychological factors, flotation, drag, the material and the design until the introduction of the model “Jammer.” As conclusions, the lack of consensus due to the variety of fields of study means that improvements in competitions are still not clarified. In addition, the change in the rules may have effects on swimmers even though they have beaten records with other swimwear. Finally, the debate concerning whether medals were won unfairly or not is proposed.
Keywords: Scopus; JCR